P206 Psychological comorbidity in vocal cord dysfunction. (2nd December 2011) - Gregson, E; Campbell, S; Lillie, S; Stacey, R; Haines, J; Fowler, S; Vyas, A
Abstract : Background: Vocal Cord Dysfunction (VCD) is typically reported to affect young females and has been associated with a psychiatric history. We run a multidisciplinary-based service for VCD patients with input from specialist speech and language therapy, physiotherapy and psychology. We investigated the demographics of our patient cohort with VCD, its association with anxiety and depression and whether this affected treatment response. Methods: All patients referred for specialist speech and language therapy at the Royal Preston Hospital Airways Clinic between June 2006 and May 2011 with VCD confirmed by endoscopy were included. During routine clinical care data were collected including demographic details and comorbidities. Patients were also asked to complete the Hospital Anxiety and Depression (HAD) questionnaire. Subjective symptomatic improvement was recorded at patient follow-up visits. Results: A total of 95 patients were eligible for study inclusion: 73.7% were female with a median age of 53 (17–83) years while men were older at 59 (37–80) years. Medical comorbidities included asthma (56.8%), reflux (47.4%), chronic cough (17.9%), nasal disease (16.8%) and neurological disease (12.6%). A history of confirmed psychiatric disease was noted in 38.9%. In 43 patients who completed HAD scores, moderate or severe anxiety was found in 41.8% and depression in 23.3%. Response to treatment was excellent (67% showing clinical improvement) and this was independent of medical or psychological comorbidity. Conclusions: Our data suggest that VCD affects a wide range of patients, in terms of age, gender, comorbidities and HAD scores which do not impact on treatment response, as a result of the multidisciplinary approach and this success is comparable to most asthma therapies when patient compliance and education are accounted for. It challenges many previously held concepts and supports a multidisciplinary approach to treating VCD.